Analisis Motivasi Belajar Fisika Peserta Didik pada Sekolah Menengah Atas - Petri Reni Sasmita; Rismar Julia Utami; Zainal Hartoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Abstract: This study aimed to analyze the students' motivation to learn physics at high school in Kerinci Regency. Methods This research is a survey research with the type of Cross-Sectional Survey. This study indicates that the average motivation for learning physics for male students is 15.50, with a standard deviation of 3.44. In contrast, female students have an average of 16.7, with a standard deviation of 2.39. In conclusion, the average learning motivation of female students is higher than that of male students, and the learning motivation of male students is significantly different compared to the explanation of female students. Keywords: Learning Motivation, Students